Therapeutic Mechanism and Effect of Camptothecin on Dextran Sodium Sulfate-Induced Ulcerative Colitis in Mice - Yizhuo Wang; Kunjian Liu; Zhiyong Qi; Tong Chen; Wei Yu; Yang Jiang; Guofeng Li; Huijie Xiao (Journal of Immunology Research)
Camptothecin (CPT) is a cytotoxic quinoline alkaloid isolated from the bark and branches of the Chinese tree Camptotheca acuminata. CPT inhibits topoisomerase I. It possesses various antitumor activities and is mainly used in the treatment of colon, ovarian, liver, and bone cancers as well as leukemia. CPT inhibits the expressions of inflammatory genes and can prevent death from chronic inflammation. Therefore, we investigated the effect of CPT treatment in ulcerative colitis (UC) using DSS-induced UC mouse model; after that, we explored its potential mechanisms. Here, we found that CPT exerted protection on DSS-induced UC in rats. In addition, the administration prominently reduced the disease activity index as well as colon length of the model rats and remarkably reduced the inflammatory cytokines. Further, CPT significantly reduced several vital proinflammatory proteins in LPS-induced RAW264.7 cells. In summary, our findings demonstrate that CPT is hopefully to act as a therapeutic agent for UC.